Impacts of the COVID-19 Pandemic on Livelihood Assets of Smallholder Agroforestry Farmers in Selected Upland Farming Communities in the Philippines - Landicho, Leila; Laruan, Kenneth A.; Abadillos , Mary Anne G.; Pascua , Romnick S. (Forest and Society, 2024)
The COVID-19 pandemic has disrupted the social and economic activities of humanity across the globe. It has created immediate negative impacts on the livelihoods and agricultural production activities of smallholder farmers. A study was conducted in 2022-2023 to assess the impacts of the pandemic on smallholder farmers engaged in vegetable-based agroforestry systems in the Philippines. Using mixed methods of data gathering such as focus group discussions, key informant interviews, and a survey of 383 smallholder agroforestry farmers, results revealed that the COVID-19 pandemic resulted in travel restrictions and lockdowns, which has caused the immobility of farmers, farm labor, farm inputs and produce. Most (80%) of the production activities of the vegetable-based agroforestry system of the smallholder farmers were affected by the pandemic because of the lack of access to farm inputs, including labor. Poor marketing of agroforestry produces and the low market prices of the produce have decreased farm income of almost all (92%) of the respondent-smallholder farmers. About 92% of farmers were not able to attend any training courses related to agroforestry during the height of the pandemic. The social capital, particularly the bonding social capital within family members and neighborhoods, was enhanced during the pandemic. This led to the exchange of planting materials, and sharing of farm inputs with fellow farmers in the four study sites. Likewise, the natural capital was enhanced since the farms, soil and the surrounding natural resources such as rivers and springs were left untouched during the pandemic. Increased production for home consumption, reduced production for markets, engaging in additional sources of income, use of organic inputs, shift to online selling, and availing loans from formal and informal credit service providers were among the coping strategies employed by the smallholder farmers. Results imply the need to future-proof smallholder agroforestry systems by developing farmers’ capacity to produce their own natural and organic fertilizers and organic pesticides; appropriate and more sustainable seed collection and storage; and expand partnerships with external organizations.